Customer priorities for water and wastewater services: a comparative evaluation of three elicitation methods. (14th July 2020) - Sayles, Rebecca; Smith, Heather M.; Jeffrey, Paul
Abstract: Water service providers are being urged to incorporate customer preferences into their investment plans with the relative merits of different elicitation techniques being exposed to greater scrutiny. Though elicitation can be undertaken with a range of methods, there is little understanding of their comparative performance in terms of being able to generate consistent or commensurable outcomes. This study reports an evaluation of both intra and inter method consistency for three preference elicitation methods. Spearman's rank correlation coefficient is used to measure consistency within and between elicitation methods and session transcripts provide additional evidence to support interpretation of the ranking process. Findings exposed low intramethod variation but significant variation in some intermethod comparisons. Discussion focuses on the internal dynamics of each method with conclusions calling for a wider range of methods to be studied so as to improve practitioner confidence in the use of these tools.